Formulation of a weakly compressible two-fluid flow solver and the development of a compressive surface capturing scheme using the volume-of-fluid approach - Heyns, Johan Adam (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012